2011
DOI: 10.1111/j.1755-5922.2011.00305.x
|View full text |Cite
|
Sign up to set email alerts
|

Bivalirudin Inhibits Periprocedural Platelet Function and Tissue Factor Expression of Human Smooth Muscle Cells

Abstract: SUMMARYAim: A major concern of stent implantation after percutaneous coronary intervention (PCI) is acute stent thrombosis. Effective inhibition of periprocedural platelet function in patients with coronary artery disease (CAD) leads to an improved outcome. In this study, we examined the periprocedural platelet reactivity after administrating bivalirudin during PCI compared to unfractionated heparin (UFH) administration. Further, the effect of bivalirudin on induced tissue factor (TF) expression in smooth musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Previous report has indicated that Bivalirudin inhibits TF expression in smooth muscle cells that constitutively express this glycoprotein [8]. In the present manuscript, we demonstrate that Bivalirudin is able to inhibit thrombin-induced TF expression in a cell population of the vessel wall never investigated before in this setting such as endothelial cells.…”
supporting
confidence: 61%
“…Previous report has indicated that Bivalirudin inhibits TF expression in smooth muscle cells that constitutively express this glycoprotein [8]. In the present manuscript, we demonstrate that Bivalirudin is able to inhibit thrombin-induced TF expression in a cell population of the vessel wall never investigated before in this setting such as endothelial cells.…”
supporting
confidence: 61%
“…In our study, the use of bivalirudin was associated with a significantly lower proportion of platelet‐rich (white) thrombus. Previous evidence suggests that ADP‐induced platelet activation is significantly lower with bivalirudin than UFH, and that bivalirudin reduces thrombin‐induced tissue factor form expression and activity . Moreover, bivalirudin does not induce the ultra‐structural changes associated with platelet activation, such as pseudopodia extrusions and increased P‐selectin expression, typically observed with UFH .…”
Section: Discussionmentioning
confidence: 92%
“…18,25 Post-transcriptional expression control regulate a variety of biologic functions, such as tumor cell invasion, thrombogenicity, metastasis, chemotaxis, growth and angiogenesis in cancer as well as in other pathophysiologic-relevant settings, such as the cardiovascular system. [15][16][17][18]26,27 Two major mechanisms modulate post-transcriptional expression: alternative splicing and micro (mi)RNAs. 16 The biogenesis of miRNAs as well as the functionality of miRNAs and alternative splicing processes were reviewed in detail elsewhere.…”
Section: Post-transcriptional Modulation Of the Tf Isoform Expressionmentioning
confidence: 99%